2022
DOI: 10.1101/2022.10.18.22281234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged Length of Hospital Stay and Associated Factors Among Patients Admitted at a Surgical Ward in Selected Public Hospitals Arsi Zone, Oromia, Ethiopia, 2022

Abstract: BackgroundProlonged length of hospital stay is the most common indicator of poor quality of health care and inefficient utilization of hospital resources. Prolonged hospital stay associated with increased mortality, hospital-acquired infection, and unnecessary utilization of hospital bed and other resources. Predicting length of hospital stay facilitates resource designing and initiates quality improvement activities. However, data regarding the prolonged length of hospital stays, and associated factors were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…There were two outcomes on this: "prolonged hospital stay" and "not prolonged". Prolonged hospital stay was de ned as hospital stay of more than the 75th percentile, according to a study that was conducted in Ethiopia (9). This was more than 5 ( ve) days in the current study.…”
Section: Variable Handlingmentioning
confidence: 95%
“…There were two outcomes on this: "prolonged hospital stay" and "not prolonged". Prolonged hospital stay was de ned as hospital stay of more than the 75th percentile, according to a study that was conducted in Ethiopia (9). This was more than 5 ( ve) days in the current study.…”
Section: Variable Handlingmentioning
confidence: 95%
“…The data were collected from adult surgical patients admitted to a surgical ward using a pretested, structured interviewer-administered questionnaire, patient chart review, and direct measurement. The data collection instrument was adapted from previously published studies [1719], whereas wealth index assessment questions were adopted from EDHS 2016 [45], and the functional status assessment tool was adopted from the Katz Index of Assessing Tool [46]. The questionnaire had sociodemographic information, wealth index assessment questions, admissions-related characteristics, clinical variables, behavioral information, and the Katz Index of functional status assessment tools.…”
Section: Methodsmentioning
confidence: 99%
“…In European hospitals, 7.98% to 16.67% of patients experienced a prolonged length of hospital stay [11][12][13]. In Asia, studies have shown that 5.4% to 30.5% of patients had prolonged hospital stays [14][15][16], and in Africa, 24.7% to 63% of patients experienced prolonged hospital stays [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations